The Elucidation of Jennette's Extreme Anxiety in Jennette McCurdy's I'm Glad My Mom Died - Rindrah Kartiningsih; Adelia Putri Oktafiani; Rommel Utungga Pasopati; Hariyono Hariyono; Kusuma Wijaya (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
This study investigates how the memoir I'm Glad My Mom Died by Jennette McCurdy portrays the characteristics of extreme anxiety in Jennette as the main character. Jennette feels such extreme anxiety due to abundant expectations from her mother to become a successful actress. Through qualitative method and explorative approach, Jennette's extreme anxiety is due to stressful and negative feelings in order to always be the best in front of her mother and other people. She knows that she hates it, but she could not avoid her mother at all. She is also terrified in her self-loathing and self-pity situation that may never meet her mother's demands. In conclusion, Jennette's extreme anxiety is haunting her alongside fear and struggle to be perfect every time.